High frequency of connexin26 (GJB2) mutations associated with nonsyndromic hearing loss in the population of Kerala, India - Joseph, Anu Yamuna; Rasool, T.J. (International journal of pediatric otorhinolaryngology, 2009)
Mutations in connexin 26 gene (GJB2) are the most common cause of hearing loss in different populations. The aim of our study was to determine the prevalence of GJB2 mutations in the population of Kerala, India. This study was conducted on the genomic DNA of 86 affected subjects and their relatives from 59 families of Kerala, India. Mutation detection was done by sequencing and PCR–RFLP. 36% of the probands had mutations in the GJB2 gene. We found that 45% (15/33) of the families that had a family history of deafness had mutations in GJB2 gene. Two different mutations were identified. W24X mutation was detected in 32.5% of the affected patients. Analysis of control samples revealed a carrier frequency of 0.0357 for this mutation. The estimation of haplotype frequency revealed that there was a significant association between the W24X mutation and the haplotype in this region with respect to the markers, D13S143 and D13S175 suggesting a founder effect for this mutation in this population. A novel mutation, R32L was detected in 3.5% of the affected patients. Structural prediction revealed that this mutation alters the helical structure of the first transmembrane domain of GJB2 protein resulting in defective gap junctions. Mutations in connexin26 is responsible for 36% of non-syndromic sensorineural deafness in the population of Kerala, India.